Online assessment literacy level of EFL teachers in Denpasar - Putra, I Kadek Krisna Dharma; Paramartha, A.A. Gede Yudha; Mahayanti, Ni Wayan Surya (Measurement In Educational Research, 2024)
This study explored the online assessment literacy (OAL) of teachers in Denpasar, focusing on categorical variables affecting literacy levels. Utilizing a descriptive quantitative approach, the research used a cross-sectional design. The population was composed of EFL teachers within the Denpasar region, data were collected from elementary to high school teachers through scored survey questionnaires. Samples were 64 EFL teachers composed of diverse demographic backgrounds. Findings indicated a predominant "Fair" level of OAL among English teachers. These results align with prior research, emphasizing the need for professional development in validity and test design. Concerns were raised about pre-service education's effectiveness in preparing teachers for digital assessments. The study underscores the importance of Online assessment literacy and suggests targeted interventions to enhance educators' assessment literacy, highlighting the necessity to adapt to evolving technological landscapes.